Proposed Business Strategy and Developing Viral Marketing Strategy for Interior Design Business Strat-Up (Case Study: Artspacie) - Aziz, Fauzan; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract.Development of the property sector in major cities other than contributes to the national GDP also open a potential market opportunities for interior design business people. Construction of houses, apartments, offices, shops, and other buildings making the ever-increasing needs of interior and product design interior design began in demand by consumers. It is not surprising that the current demand for consulting services and interior design creation is increasingly high day by day. The existence of interior design services, allows consumers to organize the room and realize their want to design the room itself.In the interior design business, number of rivals, especially from businesses that are not academically trained and dare ruining the standards set by Himpunan Desain Interior Indonesia (HDII). On the other hand, has not been conscious people to function and usability design itself so make limited market share, relative only reach the upper middle class. Marketing methods are often used in marketing design services is word of mouth. ARTSPACIE face reality if still using word of mouth or just wait for the consumer, this start-up businesses will be going nowhere and will not develop. Today, the influence of developments in technology and social media influence in selecting the reference community. This study aims to find a business strategy in the face of the digital age and collaborate on word of mouth with social media and digital marketing to develop the interior design business of ARTSPACIE.This study uses a RACE Model methods to plan, construct, and measure the effectiveness of social media used by ARTSPACIE. Viral marketing strategy use social media to increase brand awareness of a product or company in order to achieve the set targets of ARTSPACIE. Social media such as Facebook, Twitter, and Instagram is now used by ARTSPACIE to marketing the products or services. Social media should be integrated with the website ARTSPACIE to build the trust of the audiences. ARTSPACIE will use HootSuite as a tool to manage social media planning.ARTSPACIE added value in use social media as a viral marketing media, #tanyadesainer is a form of added value by providing consultation to the public for free. This strategy aims to education and promotion of ARTSPACIE. With the tagline "We Build your Ideas" is expected to emerge from the creative community and a source of inspiration ARTSPACIE in developing interior design. ARTSPACIE also expect interaction that exists in social media to realize the idea of the audience and prospective clients ARTSPACIE.ARTSPACIE takes three years to implementation of the strategic, build social media into media of viral marketing and integrating social media with ARTSPACIE websites. To increase the trust of clients, ARTSPACIE will establish offices in the second year and will recruit employees in the second year after the office standing. Whatever shape tool use, social media should be properly maintained because social media is only a tool to maximize ARTSPACIE in achieving goals and taking the opportunity of the possible market potential.Keyword: interior design, word of mouth, viral marketing, RACE Model